Somatic Embryogenesis and Genetic Uniformity of Cassava Plants Regenerated from Secondary Somatic Cotyledons Preserved in Osmotic Agents (Plant Tissue Culture and Biotechnology, 2016)
Somatic embryogenesis, plant regeneration and genetic stability of regenerants grown from cassava secondary somatic cotyledon preserved at 160C on medium containing mannitol or sorbitol alone and their combinations were investigated. Irrespective of osmotic agents in the medium, survival of cotyledon explant, frequency of somatic embryos, shoot induction, number of somatic embryo per explant, shoot elongation and rooting decreased as preservation period increased. The highest survival rate of cotyledon explants, frequency of somatic embryos, shoot induction and shoot elongation were observed on media containing 2% mannitol. However, the highest per cent rooting occurred on medium containing mannitol alone at 8 months after storage (MAS) and on media containing mannitol or sorbitol alone at 16 MAS. RAPD analysis suggested genetic uniformity among regenerants and their control plant. Osmotic preservation of secondary somatic embryos of cassava on 2% mannitol at 160C is the best slow?growth method.Plant Tissue Cult. & Biotech. 26(1): 47-54, 2016 (June)